Pengaruh Kemacetan di Jalan Raya Kopo Terhadap Perilaku Aggressive Driving Pengendara Motor - Abdul Azis; Rozanah Bayani; Warlim Isya (Jurnal Sosioteknologi, 2023)
Bandung has become Indonesia’s most congested city, based on a survey from the Asia Development Bank in October 2019. Traffic congestion can affect a person’s physical and psychological condition. This situation encourages a driver to behave aggressively to quickly reach their destination. This study aims to analyze the effect of traffic congestion on Jalan Raya Kopo on the motorcyclists’ aggressive behavior. The method used is quantitative- descriptive. Data was collected through a questionnaire distributed to 100 respondents with the criteria of motorcyclists who frequently passes Jalan Raya Kopo, aged 17-35 years. The researcher tested the classical assumptions, which included tests for normality, multicollinearity, and heteroscedasticity. Then an analysis with a simple regression analysis in the form of F test, t test, and R2 is used to analyze the effect of congestion on aggressive driving. The results showed that congestion influenced aggressive driving behavior by 28.9%, while the other 71.1% were influenced by other variables outside the test in this study.